ANALISIS KESIAPAN AKREDITASI DASAR PUSKESMAS MANGKANG DI KOTA SEMARANG - Nissa Farzana Koesoemahardja; Anneke Suparwati; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2016)
Health Minister of Indonesia Regulation No. 46 Year 2015 on Accreditation of Community Health Center is issued to guarantee the quality in primary health care level.  Mangkang Community Health Center is one of the proposed health centers represent Semarang to do the basic accreditation. However, the health center has not succeeded due to lack the role of head of community health center and across sectors also lack of assistance by the escort team so it must make improvements for the next accreditation assessment. The purpose of this study is to determine the readiness of accreditation in Mangkang community health center. The approach of this research is a qualitative descriptive. Data of this research were collected by in-depth interviews and observations. The main informants numbered 6 are head and internal staff of Mangkang community health center with the triangulans numbered 7 are the escort team of accreditation for Mangkang community health center, internal staff of Mangkang community health center, and across sectors. From the results of this research, Mangkang community health center is not ready to be accredited. It is seen from the communication process that is not running optimally in terms of dissemination of information that has not been evenly distributed, lack of understanding of staff, and inconsistent information. Resources state seen from the lack of resources such as number and competence of staff and availability of clear information to support the preparation of the accreditation as well as the characteristic disposition of the implementor is also not entirely supportive. The bureaucratic structure has been running in a good way, it can be seen from the availability and utility of SOP with regular fragmentation. The research suggest to continuously raising commitments, increase the intensity of good communication in written or unwritten between staffs in community health center, across sectors and the accreditation team of community health center. It also needs to make adjustment in number and competence of Mangkang community health center staffs.